2022
DOI: 10.3390/molecules27154675
|View full text |Cite
|
Sign up to set email alerts
|

Na2S-Mediated One-Pot Selective Deoxygenation of α-Hydroxyl Carbonyl Compounds including Natural Products

Abstract: A practical method for the deoxygenation of α-hydroxyl carbonyl compounds under mild reaction conditions is reported here. The use of cheap and easy-to-handle Na2S·9H2O as the reductant in the presence of PPh3 and N-chlorosuccinimide (NCS) enables the selective dehydroxylation of α-hydroxyl carbonyl compounds, including ketones, esters, amides, imides and nitrile groups. The synthetic utility is demonstrated by the late-stage deoxygenation of bioactive molecule and complex natural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…17 The transformation relies on the facile in situ generation of an isodiazene intermediate, which can undergo thermal homolytic N 2 extrusion to forms a new C–C bond. 17 a Inspired by N -anomeric amide's excellent electrophilic properties 17,18 and our long-term interest in organosulfur chemistry, 19 we initially programmed a project aiming at the formation of S–S bonds starting from thiols. Subsequently, we have successfully detected of disulfide product when the reaction was conducted in thiol with Levin's reagent at room temperature (Scheme 1(b)).…”
Section: Introductionmentioning
confidence: 99%
“…17 The transformation relies on the facile in situ generation of an isodiazene intermediate, which can undergo thermal homolytic N 2 extrusion to forms a new C–C bond. 17 a Inspired by N -anomeric amide's excellent electrophilic properties 17,18 and our long-term interest in organosulfur chemistry, 19 we initially programmed a project aiming at the formation of S–S bonds starting from thiols. Subsequently, we have successfully detected of disulfide product when the reaction was conducted in thiol with Levin's reagent at room temperature (Scheme 1(b)).…”
Section: Introductionmentioning
confidence: 99%
“…Preactivation/derivatization makes it easier to remove the hydroxy group but adds an extra chemical step to the synthesis. Various methods have been developed for this transformation over the past several years. Selected known methods capable of removing hydroxy groups next to an activating group are captured in Figure . A method reported by Santigo et al uses photochemical conditions for the deoxygenation of acyloins in DMSO solvent, which works via a radical pathway .…”
mentioning
confidence: 99%
“…A method reported by Santigo et al uses photochemical conditions for the deoxygenation of acyloins in DMSO solvent, which works via a radical pathway . Some other methods are also reported that work via radical pathways. , A few more methods mediated by metals are known for the reductive elimination of the hydroxy group. Each of these methods has its own advantages and limitations; to point out a few, some methods are limited only to acyloins, and some of them result in byproducts in selected substrates. …”
mentioning
confidence: 99%